“I live here, I work here, but my mind is there”: transnational families, networks and care among Venezuelan migrants - Neves dos Santos, Nícolas (2024)
Separeted venezuelan families are impacted by the health conditions of those who remained in the country. In such context, transnational families produce networks that operate remotely to help family members access medication or health care. Based on an ethnographic research carried out in São Paulo, this article aims to address the phenomenon of circulation of care in venezuelan transnational families. It describes the particular conditions of Venezuelan migration, arrangements that take place in venezuelan transnational families and aspects of reciprocity. Finally, the impacts caused by the closure of borders to contain Covid-19 are listed in order to reflect on the rights and needs of transnational families in accessing safe and effective remote care.